Mitigation of Environmental Pollution from Clinic Liquid Waste with Wastewater Treatment Installation - Fitri Amalia; Bimasri, Jhon; Wartono, Wartono (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2023)
Clinics are health service facilities which in their operations produce waste, in the form of solid and liquid waste. The waste generated is both infectious and toxic, so it needs treatment so it doesn't transmit disease and pollute the environment. This research was conducted to evaluate efforts to mitigate environmental pollution carried out by clinics by managing liquid waste generated from clinical operations. The study was conducted at the Sudirjo Partodimejo Inpatient and Outpatient Main Clinic from March to May 2023, using a qualitative descriptive method and the location was determined purposively. Collecting data were observation, interviews, and questionnaires, consisted of the volume of liquid waste, wastewater treatment, waste treatment, and the impact of pollution on society. Data analysis used simple statistical methods using Microsoft Excel 2010 software version 14.0 (C), then the results of data analysis were explained descriptively. Interview data with respondents were processed by scoring with a value 1 to 4. The scoring results were determined by scoring criteria ranging from very bad (0-35), bad (36-70), good (71-105), and very good (106-140). The clinic in 1 day produces liquid waste with a debit of 12.80 m3/day, processed use wastewater treatment plant. Community appreciated for good liquid waste management, because the quality of the discharged wastewater is below the clinical wastewater quality standards. The amount of wastewater produced by the clinic as much as 12.8 m3/day which is treated using IPAL meets hospital wastewater quality standards, and is effective in reducing the level of environmental pollution and health problems to the community around the clinic. Suggestion: Every health service facility manages liquid waste in accordance with applicable regulations and disposes of the liquid waste into water bodies after the treated waste meets wastewater quality standards. Each health service facility manages liquid waste in accordance with applicable regulations and disposes of the liquid waste into water bodies after the treated waste meets wastewater quality standards. Keywords: Waste; Environment; Health, Clinic; Pollution